PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA CV. MEKAR LESTARI KARAWANG - danang kusnanto (Value : Journal of Management and Business, 2018)
The objective of this research is to get empirical evidence and to find both a clearer understanding on a phenomenon and a conclusion about the influence of both variables to customer loyalty to CV. Mekar Lestari. The research applies descriptive and verificative method, that is; to collect, to analyze, to hypothesize and to draw conclusions, as well as to offer suggestions. Based on the result of research, it can be concluded that service quality (X1) and customer satisfaction (X2), have a significant correlation, with coefficient about 0.930 that means they have a very strong degree correlation. Service quality (X1) has a partial significant influence on customer loyalty (Y) scoring about 0.163 or 16.3%, and customer satisfaction (X2) also has a partial significant influence on customer loyalty (Y), scoring about 0.692 or 69,2%. Service quality (X1) and customer satisfaction (X2) have significant simultaneous influence on customer loyalty (Y,) scoring about 85.5%.The result of the research leads to a conclusion that customer loyalty can be influenced by service quality and customer satisfaction. This means customer loyalty can be improved by service quality and customer satisfaction.